Assessment of genetic diversity and characterization of distinctness, uniformity, and stability of newly bred sweet potato clones - YOSEP SERAN MAU; ANTONIUS S.S. NDIWA; I G.B. ADWITA ARSA; GARVASILUS V. ASA; APRIANTO NANA; JESAYAS A. LONDINGKENE; EVERT YULIANES HOSANG; NOLDY RUSMINTA ESTORINA KOTTA (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Mau YS, Ndiwa ASS, Arsa IGBA, Asa GV, Nana A, Londingkene JA, Hosang EY, Kotta NRE. 2022. Assessment of genetic diversity and characterization of distinctness, uniformity, and stability of newly bred sweet potato clones. Biodiversitas 23: 5923-5934. Genetic diversity assessment is vitally important for germplasm management and the assembly of new varieties. This study aimed to 1) assess the genetic diversity and 2) characterize the distinctness, uniformity, and stability of newly bred clones and check varieties of sweet potatoes based on morphological characters. The present study was conducted in the experimental farm of Universitas Nusa Cendana for two cycles (years) in 2021 and 2022, involving 13 newly bred (hybrid) clones and 6 control varieties. The observations were made on morphological characters of leaf, vine, and storage root, including 31 characteristics. The observed characters were given scores based on the sweet potato descriptors of IPGBR and PPVTPP. The scored morphological data were subjected to cluster analysis followed by a Principal Component Analysis to reveal the genetic diversity level. Euclidean index was used to characterize the distinctness, while the variation of the scored morphological data was used to reveal the uniformity and stability of tested genotypes. The results revealed a high genetic diversity of the studied genotypes. The cluster analysis placed the studied genotypes into four clusters; cluster I consisted of only one genotype, cluster II comprised two sub-clusters and 13 genotype members, cluster II comprised two members, and cluster IV comprised two sub-clusters and three members. The first eight principal components were responsible for about 79% of the observed variability. Euclidean distance index revealed that each of the studied genotypes is distinct from others. No off-type plant was observed; thus, each of the tested genotypes was considered uniform. Phenotypic expressions of the studied genotypes were similar over the two growing cycles; thus, each is said to be stable. The newly bred genotypes G16 and G29 genotypes that meet the distinctness, uniformity, and stability criteria based on their highest number of distinctive characters are eligible for registration as new sweet potato varieties, more specifically for their unique purplish white and purple tuber flesh characters.